Interprofessional Academic Service-Learning in Rural Australia: Exploring the impact on allied health student knowledge, skills, and practice. A Qualitative Study. - Jones, Debra; McAllister, Lindy; Lyle, David (International Journal of Practice-based Learning in Health and Social Care, 2015)
The program at the centre of this study was established in 2009 to address unmet allied health needs for rural Australian children through a primary school-based academic service-learning program. Allied health students work as interprofessional cohorts, across four school terms. Students draw on the work of previous cohorts to inform therapeutic engagement for pupils across the year. This qualitative study aimed to identify allied health student and academic expereinces and impact of program participation. One student cohort undertaking their placement in 2014 consented to particapte in interprofessional focus groups. Allied health academics participated in individual semi-structured interviews in late 2014. Data was thematically analysed with key themes and subthemes identified. This paper focuses on the interprofessional findings of; exposure challenges; the 'team continuum'; knowledge sharing between disciplines; cross-discipline collaboration; team service delivery; planning and organisation. Student acculturation and participant perceptions of desirability for interprofessional practice expereinces are also discussed. A number of limitations in the provisionof, and access to, interprofessional practice opportunities were described. Enhanced student knowledge, skills, attitutudes and resultant interprofessional practice, through participation in the prorgam, were identified by participants as program impacts.